Management in English Language Teaching - White R. Ron; Martin M. Meryyn; Stimson M. Mike; Hodge R. Robert (Cambridge, Cambridge University Press, 2001)
Teachers who are making the transition into management need to gain expertise in specialist areas such as finance, marketing and personnel. This book is the first to provide a comprehensive and practical introduction to these areas written specifically for those working in the field of English language teaching. The book is divided into three sections which deal with three key areas: People and organisations covers staff selection and development, managing curriculum development and innovation, and organising resources and information. It emphasises the importance of communication. Marketing begins by defining marketing and describing 'the marketing mix'. It goes on to offer detailed guidance for developing and implementing a marketing plan. Finance deals with the essential aspects of finance - financial records and statements, cashflow management, management accounting and using financial information - in terms which are accessible to non-specialists. The book gives clear explanations in each area supported by examples and case studies drawn from the author's own extensive experience. Each chapter contains a set of follow-up activities which reinforce and develop the content of the chapter by relating it to practical issues. The book also contains a bibliography for further reading. Management in English Language Teaching will be a valuable book for teachers whose career development is taking them to management positions as well as for more experienced managers.